‘Toshao’ as Strategic Link for Cultural Continuity and Resiliency among Amerindians During the COVID-19 Pandemic in Guyana - Chand, Susan; Thomas, Lemmel (Ethnologies, 2021)
This article focuses on the indigenous governance response to the COVID-19 pandemic in Guyana. Specifically, it explores the figure of the Toshao, the village chief, as a strategic link between the government and the indigenous peoples, the Amerindians of Guyana, in implementing government-imposed COVID-19 measures. Additionally, the study examines the role of the Toshao in maintaining or adjusting the continuity of cultural practices and resiliency among the Amerindians during the COVID-19 pandemic. We employed an exploratory qualitative approach through in-depth interviews, conducted remotely via mobile phones, with six Toshaos from various administrative regions. Some preliminary findings indicate that the Amerindians engage cultural values, traditions, and beliefs, to counteract the COVID-19 restrictions and seek alternative solutions to government-imposed measures. The leadership styles of the Toshaos are instrumental to navigate the socio-political spaces between the government and the Amerindians and, at the same time, empower them to be resilient during the pandemic. We foresee the findings of this study to be useful for policy planners to develop pandemic policies in collaboration with the Amerindians that are culture sensitive and socially friendly to them.